Fast multistation water/fat imaging at 3T using DREAM‐based RF shimming. Issue 1 (21st October 2014) - Hooijmans, Melissa T.; Dzyubachyk, Oleh; Nehrke, Kay; Koken, Peter; Versluis, Maarten J.; Kan, Hermien E.; Börnert, Peter
<x xml:space="preserve">Abstract</x> Purpose To show the effect, efficiency, and image quality improvements achievable by Dual Refocusing Echo Acquisition Mode (DREAM)‐based <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzsmbkv2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> shimming in whole‐body magnetic resonance imaging (MRI) at 3T using the example of water/fat imaging. Materials and Methods 3D multistation, dual‐echo mDixon gradient echo imaging was performed in 10 healthy subjects on a clinical 3T dual‐transmit MRI system using station‐to‐station adapted <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzsmbktj" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> shimming based on fast DREAM <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzsmbks1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> mapping. Whole‐body data were obtained using conventional quadrature excitation and station‐by‐station adapted DREAM‐based <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzsmbkpg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> shimmed excitation, along with the corresponding <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzsmbm14" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> maps for both excitation modes to assess image quality and radiofrequency (RF) performance. Results Station‐dependent DREAM‐based <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzsmbm0m" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> shimming showed significantly improved image quality in the stations covering the upper legs, pelvis, and upper body region for all subjects (P < 0.02). This finding is supported by corresponding <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzsmbkzm" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> maps showing an improved <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzsmbkx3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> homogeneity and a more precise flip angle in the DREAM‐based <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzsmbmr0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> shimmed excitation (P < 0.01). Furthermore, the very short dual‐channel DREAM <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzsmbmfb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> mapping times of less than 2 seconds facilitate quick <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzsmbmdt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> shimming. Conclusion Station‐dependent DREAM‐based <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzsmbmhc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> shimming improved RF performance and image quality and is therefore a promising technique for whole‐body multistation imaging applications. J. Magn. Reson. Imaging 2015;42:217–223. © 2014 Wiley Periodicals, Inc.